(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: To evaluate the current status of work motivation among nursing personnel at Military Hospital 175 during the year 2024. Methodology: A cross-sectional descriptive study was conducted, encompassing 302 formally contracted nurses at Military Hospital 175. Work motivation was assessed utilizing a selfadministered questionnaire comprising nine distinct evaluative dimensions. Results: The overall prevalence of perceived work motivation among nurses was 82.38%. Significant correlates of overall work motivation included age cohort, marital status, and educational attainment. Furthermore, the dimensions of direct supervisory practices, reward mechanisms, and institutional reputation demonstrated the most substantial impact on aggregate work motivation. Conclusion: Work motivation is subject to the complex interplay of multiple intrinsic personal attributes and extrinsic environmental factors. A thorough investigation of these determinants, coupled with a comprehensive and adaptable management approach tailored to the specific organizational context, is imperative for developing efficacious strategies to sustain and enhance employee work motivation.